Comparison of stellar population model predictions using optical and infrared spectroscopy. Issue 4 (28th September 2017) - Baldwin, C.; McDermid, R. M.; Kuntschner, H.; Maraston, C.; Conroy, C.
Abstract: We present Gemini/GNIRS cross-dispersed near-infrared spectra of 12 nearby early-type galaxies, with the aim of testing commonly used stellar population synthesis models. We select a subset of galaxies from the ATLAS 3D sample which span a wide range of ages (single stellar population equivalent ages of 1–15 Gyr) at approximately solar metallicity. We derive star formation histories using four different stellar population synthesis models, namely those of Bruzual & Charlot, Conroy, Gunn & White, Maraston & Strömbäck and Vazdekis et al. We compare star formation histories derived from near-infrared spectra with those derived from optical spectra using the same models. We find that while all models agree in the optical, the derived star formation histories vary dramatically from model to model in the near-infrared. We find that this variation is largely driven by the choice of stellar spectral library, such that models including high-quality spectral libraries provide the best fits to the data, and are the most self-consistent when comparing optically derived properties with near-infrared ones. We also find the impact of age variation in the near-infrared to be subtle, and largely encoded in the shape of the continuum, meaning that the common approach of removing continuum information with a high-order polynomial greatly reduces our ability to constrain ages in the near-infrared.